Physical Therapy and Dry Needling for Erectile Dysfunction and Impaired Penile Sensation Following Reconstructive Surgeries of the Penis; A Case Report - Kharaji, Ghazal; Bahramian, Mehrdad; Dabbaghipour, Narges; Molaeinezhad, Mitra; Dommerholt, Jan; Mehrad, Mehri (International Clinical Neuroscience Journal, 2022)
Peyronie’s disease (PD) is a connective tissue disorder resulting from abnormal development of fibrotic and non-expandible thickened scar tissue in the penis. Surgical intervention might lead to other complications, including decreased sensation in the penis, persistent pain after surgery, and less-rigid erections. This study presents the physiotherapeutic assessment and management of a 33-year-old man with erectile dysfunction and impaired penile sensation following reconstructive surgeries of the penis. The patient was given physiotherapeutic interventions including dry needling (DN) and subcision of the scar and stretching exercise of the penis. After the 5th visit, the patient reported improvement in symptoms. This case report suggests that dry-needling and subcision techniques can improve pain and sexual well-being in patients with post-plication surgery problems.